2021
DOI: 10.1371/journal.pone.0256957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different ischemic preconditioning strategies on physiological and cellular mechanisms of intestinal ischemia/reperfusion injury: Implication from an isolated perfused rat small intestine model

Abstract: Background Intestinal ischemia/reperfusion (I/R)-injury often results in sepsis and organ failure and is of major importance in the clinic. A potential strategy to reduce I/R-injury is the application of ischemic preconditioning (IPC) during which repeated, brief episodes of I/R are applied. The aim of this study was to evaluate physiological and cellular effects of intestinal I/R-injury and to compare the influence of in-vivo IPC (iIPC) with ex-vivo IPC (eIPC), in which blood derived factors and nerval regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Chuanminshen violaceumis polysaccharide sample (20 mg) was dissolved in 0.5 ml D 2 O for nuclear magnetic resonance (NMR) analysis. 1 H, 13 C, 1 H-1 H, Correlation Spectroscopy (COSY), Heteronuclear Singular Quantum Correlation (HSQC), and Heteronuclear Multiple Bond Correlation (HMBC) spectra were recorded on a Bruker Ascend 600 MHz Spectrometer.…”
Section: Nuclear Magnetic Resonance Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Chuanminshen violaceumis polysaccharide sample (20 mg) was dissolved in 0.5 ml D 2 O for nuclear magnetic resonance (NMR) analysis. 1 H, 13 C, 1 H-1 H, Correlation Spectroscopy (COSY), Heteronuclear Singular Quantum Correlation (HSQC), and Heteronuclear Multiple Bond Correlation (HMBC) spectra were recorded on a Bruker Ascend 600 MHz Spectrometer.…”
Section: Nuclear Magnetic Resonance Analysismentioning
confidence: 99%
“…The 13 C NMR spectrum showed that the corresponding anomeric carbons are at δ 98.55, 99.35, 99.49, 99.71, 99.58, and 99.4 ppm (Figure 2B). According to the results of methylation and NMR spectra, proton and carbon signals were confirmed at δ 61.17/3.74, 3.66; δ 61.09/3.74, 3.64; and δ 60.41-60.45/3.76-3.80.…”
Section: Fourier Transform Infrared and Nuclear Magnetic Resonance An...mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, more and more enteric bacteria have been found to have the potential to treat intestinal and extraintestinal organ damage caused by intestinal IIRI. But since the pathogenesis of IIRI is not yet fully understood, clinical treatment or prevention is mostly aimed at alleviating acute injury by simulating several links in the process of IIRI, such as ischemic preconditioning and ischemic postconditioning ( Wong et al., 2021 ; Mi et al., 2021 ).…”
Section: Overview Of Different Stressors and Effects On Intestinal Mi...mentioning
confidence: 99%
“…Atherosclerosis has been implicated in the aetiology of the overwhelming majority of cases of CMI, characterized by chronic abdominal visceral pain aggravated by meals and associated with anorexia and weight loss [ 1 ] . In most cases, CMI reflects multi-vessel chronic stable mesenteric disease, with substantial mesenteric ischaemia beyond the mitigating capacity of hypoxia adaptation [ 2 , 3 ] and the formation of collaterals [ 4 , 5 ] . By contrast, AMI reflects an acute arterial occlusion, manifested by an abrupt and catastrophic presentation.…”
Section: Introductionmentioning
confidence: 99%